2014
DOI: 10.1111/1348-0421.12202
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus infection and the risk of Sjögren or sicca syndrome: a meta‐analysis

Abstract: Previous studies have suggested an association between hepatitis C virus (HCV) infection and the development of Sjögren's syndrome (SS), also known as sicca syndrome. The main objective of this study was to summarize the existing evidence and quantitatively evaluate the association between hepatitis C virus infection and SS/sicca syndrome by performing a meta-analysis of observational studies. MEDLINE and PubMed (January 1980-August 2013) were searched to identify relevant studies in English. Outcomes were cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 60 publications
0
22
0
1
Order By: Relevance
“…Ramos-Casals et al reported that 13% of patients with chronic HCV infection in Spain also had SS [8]. A significant overall association between HCV infection and SS was observed in a recent meta-analysis [11]. There is increasing evidence from experimental [30], virological [31,32], and clinical studies [13,33,34] suggesting that HCV and SS may share some overlapping etiological characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Ramos-Casals et al reported that 13% of patients with chronic HCV infection in Spain also had SS [8]. A significant overall association between HCV infection and SS was observed in a recent meta-analysis [11]. There is increasing evidence from experimental [30], virological [31,32], and clinical studies [13,33,34] suggesting that HCV and SS may share some overlapping etiological characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…The frequent association between sicca syndrome and HCV infection has been demonstrated by both experimental and epidemiological studies focusing on the presence of chronic lymphocytic sialadenitis in patients with HCV infection [6] .…”
Section: Discussionmentioning
confidence: 99%
“…In Sjögren syndrome, the secretion ability of the lachrymal and salivary glands is impaired. The decrease in salivary volume causes a chain of oral health issues, which include soreness and friability of the oral mucosa, an increased number of dental caries, and sialadenitis of the main salivary glands [64]. Oral lichen planus is a type of mucous lesion that is not painful and thus can be easily unobserved by the patient, especially if settled in the posterior areas of the oral cavity.…”
Section: Chronic Hepatitis C Infection From An Oral Health Perspectivementioning
confidence: 99%